Anatomy of a Recharge Magma: Hornblende Dacite Pumice from the rhyolitic Tshirege Member of the Bandelier Tuff, Valles Caldera, New Mexico, USA - Boro, Joseph R.; Wolff, John A.; Neill, Owen K. (Contributions to mineralogy and petrology, 2020)
The 1.26 Ma Tshirege Member of the Bandelier Tuff is the second of two major (~ 400 km 3 , dense rock equivalent) compositionally zoned rhyolitic eruptions from the Valles caldera. Here we analyze 25 samples of a minor component of compositionally and texturally variable silicic dacite pumice (~ 67 to 72% SiO 2 ) that is widely distributed through the unit. The dacite has a phenocryst assemblage dominated by feldspar and hornblende and is presumed to be a recharge magma. Quenching of dacite against cooler rhyolite, melting of rhyolitic crystal mush, and mixing between dacite and rhyolite contributed to textural complexity. The dacite can be broken into three petrographic pumice types resulting from different degrees of dacite–rhyolite interaction. The earliest stage in the history of the dacite discernable from mineral chemistry, thermobarometry and hygrometry is mid-crustal storage at temperatures close to 900 °C and water content ~ 5 wt%. Plagioclase zoning suggests that the dacite was subject to more mafic recharge at this stage. The dacite was then injected into rhyolitic crystal mush at temperatures between 700 and 800 °C and pressures ~ 0.3 GPa. Consequences of mixing with mushy rhyolite include the following: (1) cooling and partial crystallization of dacite; (2) growth of large, dendritic feldspars with ternary compositions; (3) ingestion of and melting of feldspar and quartz from the rhyolitic mush; (4) enrichment in fluorine due to melting of biotite in the mush; (5) enrichment in light REE contents in some samples due to melting of chevkinite-rich domain(s) in the mush; (6) second boiling of quenched dacite rendering it buoyant and distributing dacite ‘enclaves’ through the zoned rhyolite magma column. The dacite was likely injected into the rhyolite over a protracted period and eventually triggered the Tshirege eruption.